Agriculture and climate change: Monitoring, reporting, and verification methodologies for agriculture, forestry, and other land use - Smukler, Sean; Palm, Cheryl (International Food Policy Research Institute, 2009)
Facilitating carbon sequestration in terrestrial ecosystems could provide a significant amount of atmospheric carbon dioxide (CO2) abatement, which is necessary to limit global temperature increases to only 2 degrees Celsius in the next century until more permanent mitigation strategies are instituted. With relatively small investments, greenhouse gas (GHG) emissions could be offset dramatically by management practices such as planting trees, reducing deforestation, midseason draining of irrigated rice, improving nitrogen fertilization efficiency, and increasing organic matter inputs to agricultural soils. Together these types of practices could add up to more than 25 percent of the combined near-term abatement strategies (including energy efficiency and low-carbon energy supply) required to stabilize emissions. While most terrestrial management potential is based on reduced deforestation and degradation (REDD), no one program can be effective in isolation. It is crucial to recognize that there are multiple competing uses for land and that maximizing GHG mitigation is not likely to be achieved with carbon-based financial incentives alone, particularly if incentives do not reach those most responsible for land management. Nearly 90 percent of the potential for terrestrial carbon capture can be found in the developing world, where land managers are largely poor farmers on small plots of land. It is imperative that these farmers be involved in carbon mitigation strategies, but dealing with numerous smallholders is an enormous challenge because planning, monitoring, reporting, and verifying mitigation creates transaction costs for carbon contracts that can be prohibitively expensive. It is therefore critical for the international community to immediately invest in the research and development of innovative methodologies to reduce transaction costs by increasing the effectiveness of monitoring, reporting, and verification for Agriculture, Forestry and Other Land Use (AFOLU) projects, particularly for smallholder agriculture in tropical regions.